Costs, outcome and cost-effectiveness of neurocritical care: a multi-center observational study - R. Raj; S. Bendel; M. Reinikainen; S. Hoppu; R. Laitio; T. Ala-Kokko; S. Curtze; M. B. Skrifvars (BMC, 2022)
Background: Neurocritical illness is a growing healthcare problem with profound socioeconomic effects. We assessed differences in healthcare costs and long-term outcome for different forms of neurocritical illnesses treated in the intensive care unit (ICU).Methods: We used the prospective Finnish Intensive Care Consortium database to identify all adult patients treated for traumatic brain injury (TBI), intracerebral hemorrhage (ICH), subarachnoid hemorrhage (SAH) and acute ischemic stroke (AIS) at university hospital ICUs in Finland during 2003-2013. Outcome variables were one-year mortality and permanent disability. Total healthcare costs included the index university hospital costs, rehabilitation hospital costs and social security costs up to one year. All costs were converted to euros based on the 2013 currency rate.Results: In total 7044 patients were included (44% with TBI, 13% with ICH, 27% with SAH, 16% with AIS). In comparison to TBI, ICH was associated with the highest risk of death and permanent disability (OR 2.6, 95% CI 2.1-3.2 and OR 1.7, 95% CI 1.4-2.1), followed by AIS (OR 1.9, 95% CI 15-23 and OR 1.5, 95% CI 1.3-1.8) and SAH (OR 1.8, 95% CI 1.5-2.1 and OR 0. 8, 95% CI 0.6-0.9), after adjusting for severity of illness. SAH was associated with the highest mean total costs ((sic)51,906) followed by ICH ((sic)47,661), TBI ((sic)43,916) and AIS ((sic)39222). Cost per independent survivor was lower for TBI ((sic)58,497) and SAH ((sic)96,369) compared to AIS ((sic)104,374) and ICH ((sic)178,071).Conclusion: Neurocritical illnesses are costly and resource-demanding diseases associated with poor outcomes. Intensive care of patients with TBI or SAH more commonly result in independent survivors and is associated with lower total treatments costs compared to ICH and AIS.